Study of performance of a 'second‐generation wavelet video encoder with a scalable rate'. Issue 4 (7th March 2019) - Hellel, Omar; Beladgham, Mohammed; Lakhdar, Abdelmounaim Moulay
Abstract : The purpose of data compression, in general, is to encode information using fewer bits than the original representation. In video coding, the goal is to reduce the bitrate of a video while preserving an acceptable quality for visual perception. In this study, the authors describe and study the performance of a proposed video coding framework that utilises a second‐generation wavelet transform specifically Spline 5/3. This framework allows for unequal error protection and has a better performance than many well know video coding systems especially for low bitrate applications. The proposed framework allows for bit rate control according to users need both at the encoder end and the decoder end, which is great for networks with variable conditions like wireless IP networks since the noise can reduce the available bandwidth and the number of users can vary from time to time.